2018
DOI: 10.2196/10063
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Survey Assessing the Attitudes of Health Care Professionals in Germany Toward the Use of Telemedicine in Pregnancy Monitoring: Cross-Sectional Study

Abstract: BackgroundThe demand for fetal monitoring and constant reassurance is high in pregnant women. Consequently, pregnant women use various health apps and are more likely to visit emergency departments due to subjective but nonurgent complaints. However, electronic health (eHealth) and mobile health (mHealth) solutions are rarely used to prevent nonurgent emergency consultations. To implement modern care solutions, a better understanding of the attitudes, fears, and hopes of health care professionals toward eHealt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 42 publications
3
32
0
1
Order By: Relevance
“…Furthermore, pregnant women had their own viewpoints focusing on their individual situations, but they were more positive and considered more opportunities from remote monitoring compared with the staff members (Runkle, Sugg, Boase, Galvin, & Coulson, ). The findings of this study confirm other current research, such as Grassl et al (), who also found healthcare providers had ambivalent and sceptical attitudes towards remote monitoring in obstetrics; in other studies, pregnant women gave mainly positive feedback on remote self‐monitoring (Krishnamurti et al, ; Schramm et al, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, pregnant women had their own viewpoints focusing on their individual situations, but they were more positive and considered more opportunities from remote monitoring compared with the staff members (Runkle, Sugg, Boase, Galvin, & Coulson, ). The findings of this study confirm other current research, such as Grassl et al (), who also found healthcare providers had ambivalent and sceptical attitudes towards remote monitoring in obstetrics; in other studies, pregnant women gave mainly positive feedback on remote self‐monitoring (Krishnamurti et al, ; Schramm et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…In the future, it is important to use new technological solutions in cooperation with end users; they need to be able to trust the new devices and applications (Grym et al, ). Young healthcare professionals, in particular, have favourable attitudes and recognize the potentials of modern technology (Grassl et al, ); thus, the future implementation of technological innovations could become easier and more natural.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, despite the undoubted potential of telemedicine in O&G, many healthcare professionals remain sceptical, due to fear of late presentation of emergencies, lack of personalised care and concern regarding the replacement of the human workforce by machines. 10 Telemedicine can also facilitate training and education, and contribute towards continued professional development. For example, remote feedback from experienced surgeons during real-time surgery has been shown to provide a cost-effective method of learning with a similar efficacy and safety profile as in-person mentoring.…”
Section: Telemedicine In Obstetrics and Gynaecologymentioning
confidence: 99%
“…4 At the same time, the demand for fetal monitoring and constant reassurance is high amongst pregnant women. 5 Telemedicine applications in obstetrics can be categorized depending on the form of service provided (educational, teleconsultations, remote monitoring) or depending on the problem addressed (lifestyle issues, gestational diabetes, mental health, etc.). Many of the applications have been tested in the past few years and positive effects have been shown (reviewed by van den Heuvel et al 6 ); however, most of the studies lack an endpoint related to its clinical impact, which still remains to be determined.…”
Section: Introductionmentioning
confidence: 99%